Microservice patterns and best practices : explore patterns like CQRS and event sourcing to create scalable, maintainable, and testable microservices /: explore patterns like CQRS and event sourcing to create scalable, maintainable, and testable microservices. (2018) - Pacheco, Vinicius Feitosa
No abstract available